REPRESENTASI KEKERASAN SEKSUAL TERHADAP PEREMPUAN DALAM FILM VINA: SEBELUM 7 HARI - Muhammad Fuad Hasan; Zahrotus Sa'idah (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This research aims to describe the representation of sexual violence against women in the film Vina: Before 7 Days and its impact on public perception, as well as to contribute to filmmakers in depicting sensitive issues. The urgency of this research lies in the importance of increasing public awareness of the issue of sexual violence which continues to increase. The method used is a qualitative approach with semiotic analysis techniques based on John Fiske's perspective, which focuses on the interaction of signs and audiences in a cultural context. The main data consists of scenes in films that show sexual violence, supported by secondary data from news articles and journals. Data collection techniques include non-participant observation, literature study, and documentation, while analysis is carried out using the Miles & Huberman method, which includes data condensation, data presentation, and drawing conclusions using theoretical triangulation. The results of this research show that the film "Vina: Prior 7 Hari" displays two scenes of sexual violence against women, namely harassment in the women's bathroom and rape by a motorbike gang, which is analyzed through John Fiske's semiotic theory, showing the reality of sexual violence, criticism of norms society, patriarchal domination, and social apathy which are reflected in reflective, intentional, and constructionist representations.